2022
DOI: 10.1002/jmv.27944
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal immune recovery and associated factors among people living with HIV/AIDS on second‐line antiretroviral therapy in central China: A retrospective cohort study

Abstract: The introduction and scale-up of antiretroviral therapy (ART) have contributed to significantly improved patients with acquired immune deficiency syndrome (AIDS) quality of life and prolongs their survival. This has occurred by suppressing viral replication and recovering the CD4 cell count. However, some patients do not normalize their CD4 cell count, despite suppression of the viral load (VL). Patients with suboptimal immune recovery (SIR), as defined by a VL < 400 copies/ml with a CD4 cell count of<200 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Here, we find that single/window individuals are a risk factor for failure in second-line ART, which is consistent with some research findings. For example, A multivariable analysis showed that single status (unmarried or divorced) was a risk factors for PLHIV with second-line ART [25]. Older age was a higher risk of death, we report that the HR of death among PLHIV older than 50 years was 2.56 times that of those under 40, patients with 40-50 years old was not show higher HR of death compared with those under 40.…”
Section: Discussionmentioning
confidence: 53%
“…Here, we find that single/window individuals are a risk factor for failure in second-line ART, which is consistent with some research findings. For example, A multivariable analysis showed that single status (unmarried or divorced) was a risk factors for PLHIV with second-line ART [25]. Older age was a higher risk of death, we report that the HR of death among PLHIV older than 50 years was 2.56 times that of those under 40, patients with 40-50 years old was not show higher HR of death compared with those under 40.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, ART can reduce viral load of HIV-infected individuals and therefore reduce sexual transmission [28][29][30]. The updated Chinese guidelines for diagnosis and treatment of HIV/AIDS (2018) recommend early initiation of ART for HIV prevention.Zhu XY et al [31] conducted a study on the timeliness of ART for HIV infected individuals in Shandong Province, which showed that young people aged 15-24 were less likely to accept ART timely. However, there has not study to nd the reasons of HIV-infected students delaying in accepting HIV care continuum up to now.This study analyzed the epidemiological characters and HIV care status of HIV-infected students in Shandong province during 2017 to 2019, and explored the in uencing factors of student cases accepting CD4 test and ART during 30 days after diagnosis.…”
mentioning
confidence: 99%
“…Zhu XY et al [31] conducted a study on the timeliness of ART for HIV infected individuals in Shandong Province, which showed that young people aged 15-24 were less likely to accept ART timely. However, there has not study to nd the reasons of HIV-infected students delaying in accepting HIV care continuum up to now.…”
mentioning
confidence: 99%